2002
DOI: 10.1007/s00442-002-0958-9
|View full text |Cite
|
Sign up to set email alerts
|

14C transfer between the spring ephemeral Erythronium americanum and sugar maple saplings via arbuscular mycorrhizal fungi in natural stands

Abstract: We investigated in the field the carbon (C) transfer between sugar maple (Acer saccharum) saplings and the spring ephemeral Erythronium americanum via the mycelium of arbuscular mycorrhizal (AM) fungi. Sugar maple saplings and E. americanum plants were planted together in pots placed in the ground of a maple forest in 1999. Ectomycorrhizal yellow birches (Betula alleghaniensis) were added as control plants. In spring 2000, during leaf expansion of sugar maple saplings, the leaves of E. americanum were labelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 29 publications
4
60
0
Order By: Relevance
“…Numerous studies have shown that AM fungi can enhance the P nutrition of host plants, increase the diversity and stability of plant communities, and enhance the resistance of host plants to abiotic stresses such as drought and salt stress [16,[41][42][43] . Until now, few studies have been carried out on the mycorrhizal status of ephemeral plants that play an important role in the stability of desert ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that AM fungi can enhance the P nutrition of host plants, increase the diversity and stability of plant communities, and enhance the resistance of host plants to abiotic stresses such as drought and salt stress [16,[41][42][43] . Until now, few studies have been carried out on the mycorrhizal status of ephemeral plants that play an important role in the stability of desert ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Forest ecosystems are dynamic, and this is illustrated by dynamic patterns and processes in mycorrhizal networks. Not only do the complexity and composition of mycorrhizal networks change over time (Twieg et al, 2007), but belowground fluxes of nutrients change over the growing season with shifts in source-sink gradients among networked plants (Lerat et al, 2002). Using dual 13 C/ 14 C labelling in the field, Philip (2006) found that the direction of net carbon transfer reversed twice over the growing season: (1) from shooting Douglas-fir to bud-bursting birch in spring; (2) then reversing, from nutrient and photosynthateenriched paper birch to stressed understory Douglas-fir in summer; and (3) reversing again, from still-photosynthesizing Douglas-fir to senescent paper birch in the fall.…”
Section: Role Of Mycorrhizal Network In Forest Stability With Climatmentioning
confidence: 99%
“…Complex systems are dynamic, and this is illustrated by dynamic patterns and processes in mycorrhizal networks. Not only do the complexity and composition of mycorrhizal networks change over time (Twieg et al 2007), but below-ground fluxes of nutrients change over the growing season with shifts in source-sink gradients among networked plants (Lerat et al 2002). Using dual 13 C/ 14 C labelling in the field, Leanne Philip found that the direction of net carbon transfer reversed twice over the growing season: (1) from shooting Douglas-fir to bud-bursting birch in spring; (2) then reversing, from nutrient and photosynthate-enriched paper birch to stressed understory Douglas-fir in summer; and (3) reversing again, from still-photosynthesizing Douglasfir to senescent paper birch in the fall (Philip 2006) (Fig.…”
Section: Mycorrhizal Network In Complexmentioning
confidence: 99%